Biocontrol of Rhizoctonia solani via Induction of the Defense Mechanism and Antimicrobial Compounds Produced by Bacillus subtilis SL-44 on Pepper (Capsicum annuum L.) - Wu, Zhansheng; Huang, Yuanyuan; Li, Yan; Dong, Jiawei; Liu, Xiaochen; Li, Chun (Frontiers in Microbiology, 2019)
Pepper seedling wilt disease is the main cause of crop yield reduction. Biocontrol agents are widely used to control plant diseases caused by pathogenic fungi, and activate plant defense systems. Our preliminary work showed that Bacillus subtilis SL-44 played a significant role in the reduction of wilt disease severity on pepper plants. To evaluate biological control mechanism of B. subtilis SL-44 on wilt disease caused by Rhizoctonia solani, the activities of the related enzymes were detected in the pepper seedling with different treatment in this study. Fluorescence microscopy combined with different dyes showed that B. subtilis SL-44 induced a large amount of active oxygen and callose accumulation in pepper leaves. The defense-related enzymes activities in pepper were improved significantly when treated with B. subtilis SL-44, including peroxidase, catalase, superoxide dismutase, polyphenol oxidase and phenylalanine ammonia lyase. The activity of chitinase and β-1,3-glucanase in B. subtilis SL-44 treated pepper was also enhanced. Furthermore, the pepper resistance gene CaPIN II expression level was significantly increased in B. subtilis SL-44 treatment. Besides, B. subtilis SL-44 filtrate led to the death of the pathogenic fungus by fracturing the mycelia and leaking of the cell contents. Surfactin, iturin and fengycin were found in B. subtilis SL-44 crude extracts which could be effective antifungal compounds against R. solani. The results suggest that B. subtilis SL-44 could not only activate Induced Systemic Resistance of pepper seedling against wilt disease caused by R. solani. by Jasmonic acid-dependent signaling pathway, but also produce antifungal compounds to inhibit or even damage the mycelium growth of R. solani. The findings of this study provide novel guidance in plant protection development.